Educação e autonomia: O processo de formação moral em Immanuel Kant - Penha, Patricia Silveira (2019)
This research aims to present a relationship between Autonomy and Pedagogy from a study of the works of Immanuel Kant (1724-1804), such as the Groundwork of the Metaphysics of Morals , Metaphysics of Morals, On Education, among other writings. Initially, we will carry out a study of how the development of human history occurred, emphasizing as the main point of departure the passage from nature to sociability, from the writings Conjectural Beginning of Human History (1786), An Answer to the Question: "What is Enlightenment? "(Aufklärung) (1784), What Does it Mean to Orient Oneself in Thinking (1786) and Idea for a Universal History with a Cosmopolitan Purpose (1784). Then, in order to make explicit the process of leaving a state of submission to freedom, we will use a part of the Critique of Pure Reason (1781) and the Groundwork of the Metaphysics of Morals (1785), in order to demarcate the transition from natural causation to the free causality, emphasizing in what way freedom is conceived in the scope of morality, that is, as autonomy of the will, a spontaneity that acts independently of external causes. Therefore, we will discuss some concepts that contribute to think of an autonomy of the subject from the Doctrine of Law and the Doctrine of Virtue of the work Metaphysics of Morals (1797), demonstrating how freedom in the sphere of law and morality. Finally, we will discuss how the process of the formation of human autonomy in On Education (1803) occurs. Therefore, we can observe that autonomy and education are indispensable to the process of morality, as well as the construction of a being capable of guiding their actions with the use of reason.